ACCOUNTING PROCEDURE AND MANAGEMENT CASH WAQF IN INDONESIAN WAQF INSTITUTIONS - Laela Fitria Perdana; Dewi Susilowati; Christina Tri Setyorini (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2018)
This paper aims to explore the management and reporting of cash waqf in Indonesia Waqf Institutions. The methodology used in this study is qualitative descriptive research with case study approach to explain specifically about the management and reporting of cash Waqf. The results of this study indicate that the management of cash waqf in Dompet Dhuafa has fulfilled the waqf principle that adopted from the principle of BCPs corresponds to laws and regulations. On the contrary, at the Representative of Indonesian Waqf Board (BWI) in Banyumas Regency as the representative of waqf regulator, its management of waqf is not yet optimal. Dompet Dhuafa reports their waqf management in financial statement, while at Representative of Indonesian Waqf Board in Banyumas Regency did not report management of cash waqf.